Cross-Cultural Validity of the Child and Adolescent Dispositions Model in a Clinical Sample of Children With Externalizing Behavior Problems - Del Giudice, Teresa; Tervoort, Janina; Hautmann, Christopher; Walter, Daniel; Döpfner, Manfred (Frontiers in Psychology, 2020)
Background: The Child and Adolescent Dispositions Scale—parent rating (CADS-P) explores three emotional dispositions that may enlarge the probability of future externalizing problem behavior. The English version has proven its psychometric quality within a population-based sample of children and adolescents. The presents study investigates the German version of the CADS-P by examining a clinically referred sample of children with externalizing behavior problems. Methods:The sample included 132 children aged 4–11 years with a diagnosis of attention- deficit/hyperactivity disorder (ADHD) or oppositional defiant disorder (ODD). The factor structure of the CADS-P was evaluated using exploratory (EFA) and confirmatory factor analyses (CFA). Reliability was estimated using internal consistency (Cronbach's alpha). Validity was assessed through linear regression analyses, with symptoms of externalizing [conduct disorder (CD), ODD, ADHD] and internalizing behavior problems (anxiety, depression) as criterion variables and the three CADS-P factor scores as predictors. Results:After eliminating eight items due to insufficient psychometric properties, EFA and CFA supported a three-factor solution for the German CADS-P. Cronbach's alpha coefficient exceeded α = 0.70 for all subscales. Mostly, as predicted, the CADS-P dimensions were associated with symptoms of ODD/CD and ADHD and symptoms of anxiety and depression. Conclusions:The present study provides evidence for the cross-cultural validity of the CADS- P in a non-English-Speaking country. Results show that the German version of the CADS-P is a reliable and valid parent questionnaire for assessing prosociality, negative emotionality and daring as emotional dispositions that may enlarge the probability to develop externalizing problem behavior. Trial Registration: The study was approved by the review board of the Medical Faculty of the University of Cologne (ID 09-123) and was pre-registered at ClinicalTrials.gov (ID: NCT01350986).